False belief understanding and “cool” inhibitory control in 3-and 4-years-old Italian children - Bellagamba, Francesca; Addessi, Elsa; Focaroli, Valentina; Pecora, Giulia; Maggiorelli, Valentina; Pace, Beatrice; Paglieri, Fabio (Frontiers in Psychology, 2015)
During preschool years, major developments occur in both executive function and theory of mind (ToM), and several studies have demonstrated a correlation between these processes. Research on the development of inhibitory control (IC) has distinguished between more cognitive, “cool” aspects of self-control, measured by conflict tasks, that require inhibiting an habitual response to generate an arbitrary one, and “hot”, affective aspects, such as affective decision making, measured by delay tasks, that require inhibition of a prepotent response. The aim of this study was to investigate the relations between 3- and 4-year-olds’ performance on a task measuring false belief understanding, the most widely used index of ToM in preschoolers, and two tasks measuring cognitive versus affective aspects of IC. To this end, we tested 101 Italian preschool children in three tasks: (a) the Unexpected Content False Belief task, (b) the Conflict task (a simplified version of the Day-Night Stroop task), and (c) the Delay task. Children’s receptive vocabulary was assessed by the Peabody Picture Vocabulary test. Children’s performance in the False Belief task was significantly related only to performance in the Conflict task, controlling for vocabulary and age. Importantly, children’s performance in the Conflict task did not significantly correlate with their performance in the Delay task, suggesting that these tasks measure different components of IC. The dissociation between the Conflict and the Delay task may indicate that monitoring and regulating a cool process (as flexible categorization) may involve different abilities than monitoring and regulating a hot process (not touching an available and highly attractive stimulus). Moreover, our findings support the view that “cool” aspects of IC and ToM are interrelated, extending to an Italian sample of children previous findings on an association between self-control and ToM.